Fine needle aspiration biopsy of an osteoclast-rich undifferentiated urothelial carcinoma: A cytology case report and review of the literature - Purohit, Chetna N. (Medknow Publications, 2010)
Osteoclast-rich undifferentiated carcinoma of urinary bladder (ORUCUB) is a very rare and an unusual variant of high-grade urothelial carcinoma. Here, we report an extraordinary case of metastatic ORUCUB, diagnosed by fine needle aspiration (FNA) biopsy, in a 74-year-old Hispanic male who presented with a palpable, tender left groin mass and a known previous history of high-grade carcinoma of urinary bladder and prostatic cancer. To the best of our knowledge, diagnosis of ORUCUB by FNA is the first case report in FNA cytology to be published to date. A review of the literature is emphasized on the cytological, histological and immunohistochemical features and differential diagnoses of giant cell tumor.